Therapeutic Versatility of Resveratrol Derivatives - Nawaz, Waqas; Zhou, Zhongqin; Deng, Sa; Ma, Xiaodong; Ma, Xiaochi; Li, Chuangang; Shu, Xiaohong (Nutrients, 2017)
Resveratrol, a natural phytoalexin, exhibits a remarkable range of biological activities, such as anticancer, cardioprotective, neuroprotective and antioxidant properties. However, the therapeutic application of resveratrol was encumbered for its low bioavailability. Therefore, many researchers focused on designing and synthesizing the derivatives of resveratrol to enhance the bioavailability and the pharmacological activity of resveratrol. During the past decades, a large number of natural and synthetic resveratrol derivatives were extensively studied, and the methoxylated, hydroxylated and halogenated derivatives of resveratrol received particular more attention for their beneficial bioactivity. So, in this review, we will summarize the chemical structure and the therapeutic versatility of resveratrol derivatives, and thus provide the related structure activity relationship reference for their practical applications.